PENGENALAN DASAR HTML DAN CSS: LANGKAH PERTAMA DALAM PENGEMBANGAN WEB - Andhika Mardiansyah; Bayu Nur Kasah; Haidar Rasyid Zamzami; Muh Yasin Arabu; Mikail Abdullah Nasro; Noval Kristanto; Rachma Paojiah; Yesi Wulandari (Abdi Jurnal Publikasi, 2025)
HTML (Hypertext Markup Language) and CSS (Cascading Style Sheets) are the foundational technologies for web development. Learning HTML and CSS is essential for building and designing web pages. HTML provides the structure of a webpage, while CSS is used for designing and layout purposes. Understanding these technologies is important for students to gain the necessary skills to create functional and attractive websites. This paper aims to introduce the basics of HTML and CSS to students, guiding them through the steps involved in web development, and enabling them to create their own web pages.